2004
DOI: 10.1128/mmbr.68.2.320-344.2004
|View full text |Cite
|
Sign up to set email alerts
|

ERK and p38 MAPK-Activated Protein Kinases: a Family of Protein Kinases with Diverse Biological Functions

Abstract: Conserved signaling pathways that activate the mitogen-activated protein kinases (MAPKs) are involved in relaying extracellular stimulations to intracellular responses. The MAPKs coordinately regulate cell proliferation, differentiation, motility, and survival, which are functions also known to be mediated by members of a growing family of MAPK-activated protein kinases (MKs; formerly known as MAPKAP kinases). The MKs are related serine/threonine kinases that respond to mitogenic and stress stimuli thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
1,861
10
18

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,158 publications
(1,963 citation statements)
references
References 253 publications
(369 reference statements)
30
1,861
10
18
Order By: Relevance
“…When cells are exposed to various extracellular stimuli, ERK can be activated via dual phosphorylation of the TEY motif at threonine and tyrosine residues by upstream MAPKKs. Subsequently, activated ERK proteins are translocated into the nucleus and regulate the expression of ERK pathway-target genes [14,17,18]. In the present study, subcellular location analysis revealed that the green fluorescence of ChERK was mainly distributed in the cytoplasm of HEK293T cells (Fig.…”
Section: Cherk Was Mainly Localized In the Cytoplasm Of Hek293t Cellssupporting
confidence: 52%
See 1 more Smart Citation
“…When cells are exposed to various extracellular stimuli, ERK can be activated via dual phosphorylation of the TEY motif at threonine and tyrosine residues by upstream MAPKKs. Subsequently, activated ERK proteins are translocated into the nucleus and regulate the expression of ERK pathway-target genes [14,17,18]. In the present study, subcellular location analysis revealed that the green fluorescence of ChERK was mainly distributed in the cytoplasm of HEK293T cells (Fig.…”
Section: Cherk Was Mainly Localized In the Cytoplasm Of Hek293t Cellssupporting
confidence: 52%
“…In the ERK signaling pathway, MEK is the upstream activator of ERK and Raf is the upstream activator of MEK. Upon stimulation, Raf, MEK and ERK sequential activation results in ERK translocation from the cytoplasm to the nucleus where it phosphorylates numerous transcription factors that induce the expression of ERK pathway-target genes [14,17,18]. In mammals, the family of ERK kinases is divided into two groups based on their protein structure: classic MAP kinases (ERK1 and ERK2) and large MAP kinases (ERK3, ERK5, ERK7 and ERK8).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, suppression of the pathways of p44/42 and p38 MAPKs, pAkt and p-NF-jB by bufalin could be responsible for the reduction of COX-2 expression in A549 cells. The ERK1/2 and p38 MAPK signaling pathways can be activated in response to a diverse range of extracellular stimuli including mitogens, growth factors, and cytokines (Baccarini 2005;Meloche and Pouysségur 2007;Roux and Blenis 2004) and are important targets in the diagnosis and treatment of cancer (Roberts and Der 2007). Suppression of the activated EGFR and ERK1/2 and p38 MAPKs as well as Akt signaling pathways led to inhibition of the proliferation of A549 cells (Baldys et al 2007;Nguyen et al 2004;Recchia et al 2009;Su et al 2010).…”
Section: Bufalin Reduces the Receptor Phosphorylation And/or Proteinmentioning
confidence: 99%
“…Once present in the cell cytosol, EF and LF damage the cell in various ways; LF is a zinc-dependent metalloproteinase that cleaves and inactivates the mitogen-activated protein kinase (MAPK) kinases 1–4, 6 and 7 [6]. The cleavage events result in inactivation of the MAPK pathways thereby hampering a variety of cellular responses including cell division, apoptosis, and survival [7]. EF is a calmodulin-dependent adenylyl cyclase that elevates intracellular cAMP levels by converting ATP to cAMP, the classical second messenger, thereby causing diverse adverse side-effects [8].…”
Section: Introductionmentioning
confidence: 99%